Debate on methodology of renewing Muslim Law: a search for a synthetic approach - Haneef, Sayed Sikandar Shah (Berkely, 2010)
Islamic law as a sum total of juristic views believed and practices by Muslims, by and large, is locked in interpretations made by legal scholars of the medieval ages. To relate it to contemporary needs of the Ummah, Muslims thinkers have been entangled with the question of its renewal for the past two centuries. In this pursuit, the most thorny question has surrounded the methodology of accomplishing such a renewal. This has given rise to main three trends, namely traditionalists, modernists and liberal approaches to renewal of Islamic law. This paper, however, argues that rejuvenating Muslim religious law requires a synthetic method rather than a bigoted exclusivist approach as advocated by proponents of renewal in our time.